Reactor Safety Gap Evaluation of Accident-Tolerant Components and Severe Accident Analysis. (1st November 2016) - Farmer, M. T.; Bunt, R.; Corradini, M.; Ellison, P.; Francis, M.; Gabor, J.; Gauntt, R.; Henry, C.; Linthicum, R.; Luangdilok, W.; Lutz, R.; Paik, C.; et al.
Abstract: The reactor accidents at Fukushima Daiichi have rekindled interest in light water reactor (LWR) severe accident phenomenology. Postevent analyses have identified several areas that may warrant additional research and development (R&D) to reduce modeling uncertainties and assist industry in the development of mitigation strategies and in the refinement of severe accident management guidelines to both prevent significant core damage given a beyond-design-basis event and mitigate source term release if core damage does occur. On these bases, a technology gap evaluation on accident-tolerant components and severe accident analysis methodologies was completed with the goal of identifying any data and/or knowledge gaps that may exist given the current state of LWR severe accident research and augmented by insights gained from recent analyses of the Fukushima Daiichi accident. The ultimate benefit of this activity is that the results can be used as a basis for refining research plans to address key knowledge gaps in severe accident phenomenology that affect reactor safety and that are not being directly addressed by the nuclear industry or the U.S. Nuclear Regulatory Commission. As a result of this study, 13 gaps were identified in the areas of severe accident—tolerant components and accident modeling. The results clustered in three main areas: (1) modeling and analysis of in-vessel melt progression phenomena, (2) emergency core cooling system equipment performance under beyond-design-basis accident conditions, and (3) ex-vessel debris coolability and core-concrete interaction behavior relevant to accident management actions. This paper provides a high-level summary of the methodology used for the evaluation, the identified gaps, and, finally, the appropriate R&D that may be completed to address the gaps.